Regularities of crustal faulting and tectonophysical indicators of fault metastability - Yu. L. Rebetsky (Геодинамика и тектонофизика, 2018)
The problem of forecasting seismic hazards is discussed. The stress state data characterizing various aspects of brittle failure are reviewed in detail. It is shown that the most convenient tool for analyzing such data is the Mohr stress diagram and the Coulomb criterion. Noted is the role of a fluid in not only reducing the normal stresses responsible for brittle failure, but also predetermining the major processes in fault zones. In each fault body, a node can be distinguished as a fault part wherein the main structural and material transformations take place. The node contains narrow elongated zones of modification of mylonites, from protomylonites to ultramylonites and blastomylonites, that are related to the localization of continuous and discontinuous shear deformation. Due to the metamorphic processes, fault zones are less strong than the surrounding consolidated blocks of the crust. A theoretical analysis of the mechanism of displacements along the discontinuities of different scale ranks shows differences in their manifestation. Tectonic and seismic displacements along the rupture occupy the entire area at once, while displacements along the fault zone occur in stages along its extent and follow the ‘rolling-carpet’ principle that is also typical of intra-crystal dislocations. The stress state in the vicinity of ruptures and faults has different characteristic features. Based on the seismological and tectonophysical data on earthquake focal parameters and discontinuities, it is possible to identify two or three ranks of stresses, which differ in the laws predetermining their mutual relationships. Actually, this conclusion contradicts the hypothesis of self-similarity of discontinuities in their continuous range, from a dislocation to a fault zone, which length amounts to tens of kilometers. Besides, it imposes a restriction on the use of statistical analysis of seismic data. The seismic data show that in the source of a large earthquake, displacement develops as a running band (‘rolling-carpet’ principle). In the source of a weak earthquake, it occupies the entire earthquake focal area at once. The differences in the types of shearing in the sources of weak and strong earthquakes are related to the relationships between three dynamic parameters of the medium: velocity of seismic wave propagation, rate of rupture propagation, and displacement rate of the sides of the fracture. Using tectonophysical methods, the stress state was reconstructed for the seismically active regions of the planet and the sources of the mega-earthquakes of the 21st century. Based on the reconstructions, the mean strength and stress values were calculated, and the specific features of the stress fields were revealed. It is established that the strongest regional earthquakes ‘avoided’ the areas with increased effective isotropic pressure. The sizes of the sources of the strongest earthquakes were controlled by the size of the region with decreased effective pressure. The sites, wherefrom the earthquake were initiated, were often located in the zones of the highest stress gradients. These regularities support the term “metastability of the state of fault zone” (introduced to seismology from the physics of the states of matter) and justify it by a specific distribution pattern of stress values prior to the mega-earthquake. Based on the tectonophysical definition of the metastable state of faults, the important role is outlined for a stress gradient zone that represents a location wherein a trigger earthquake occurs. The ‘maturity’ of the zone with increased stress gradient values is, in essence, a characteristic of the time interval of metastability of the fault zone.